Startle disease-two sibling cases - Elkay, Mürüvet; Incecik, Faruk; Hergüner, M Ozlem; Leblebisatan, Göksel; Altunbaşak, Sakir (The Turkish Journal of Pediatrics, 2005)
Startle disease (hyperekplexia) is a rare non-epileptic disorder characterized by hypertonia, generalized stiffness and brief muscle jerks in response to unexpected auditory, somatosensory and visual stimuli. In this paper, two siblings with generalized stiffness and sudden muscle jerks to unexpected stimuli of various types are presented. They were previously misdiagnosed as epilepsy and treated with the conventional antiepileptic drugs. We wanted to call attention to and increase awareness of this rare disease and its differential diagnosis to avoid unnecessary investigations and treatment.